Development of jaspine b analysis using lc-ms/ms and its application: Dose-independent pharmacokinetics of jaspine b in rats - Song, Im Sook; Jeon, Ji Hyeon; Lee, Jihoon; Lim, Dong Yu; Lee, Chul Haeng; Lee, Dongjoo; Choi, Min Koo (Analytical Science and Technology, 2021)
A rapid and simple LC-MS/MS analytical method in determining Jaspine B has been developed and validated in rat plasma. The standard curve value was 25 – 5000 ng/mL and the linearity, inter-day and intra-day accuracy and precision were within 15.0 % of relative standard deviation (RSD). The mean recoveries of Jaspine B ranged from 87.5 % to 91.2 % with less than 3.70 % RSD and the matrix effects ranged from 91.1 % to 108.2 % with less than 2.6 % RSD. The validated LC-MS/MS analytical method of Jaspine B was successfully applied to investigate the dose-escalated pharmacokinetic study of Jaspine B in rats following an intravenous injection of Jaspine B at a dose range of 1 – 10 mg/kg. The initial plasma concentrations and area under plasma concentration curves showed a good correlation with intravenous Jaspine B dose, indicating the dose independent pharmacokinetics of Jaspine B in rats. In conclusion, this analytical method for Jaspine B can be easily applied in the bioanalysis and pharmacokinetic studies of Jaspine B, including its administration at multiple therapeutic doses, or for making pharmacokinetic comparisons for the oral formulations of Jaspine B in small experimental animals as well as in vivo pharmacokinetic–pharmacodynamic correlation studies.
Keywords: Dose escalation; Jaspine B; Liquid chromatography-tandem mass spectrometry; Pharmacokinetics; Rat